Linguistics in punning the creation and interpretation of Puns in Chaucer's Wife of Bath's Tale - Laguidao, Cherry Lynn L.; Epistola, Nieves B. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 1997)
This study is concerned with puns 0 its creation and interpretation. By looking more closely at this unilinguistic wordplay through its internal structures, characteristics and relationship to context, the analysis shows that puns are relevant to our understanding of the workings of language. This study further proves that despite the ambiguity it sets up, it shows that it ios utilized by many great writers. One of them is Geoffrey Chaucer whose puns in his work The Wife of Bath's Tale are here reviewed and interpreted. Subsequently, this study tries to establish the fact that puns are linguistic data that should not be ignored because their analysis requires and exemplifies concepts that are central in normal language use.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.